Using the balanced scorecard as a tool for performance management of higher education degrees - Cardoso, E.; Trigueiros, M. J. (13th International Conference of European University Information Systems (EUNIS 2007), 2007)
This paper describes the application of the Balanced Scorecard (BSC) as a tool for performance management of Higher Education degrees. A generic performance management framework has been developed using the BSC as a strategic management system that enables the different stakeholders to effectively execute and monitor the strategy outlined for the degree. The cascading process of the high-level BSC of the degree’s coordination into the lower-level BSC of individual courses will be detailed. The MSIAD degree – a Master degree in Integrated Decision Support Systems lectured in the Department of Information Sciences and Technologies of ISCTE will be used to exemplify the application of the generic BSC framework.